ANALISA THERMAL KOLEKTOR SURYA PELAT DATAR YANG DILENGKAPI PCM CAMPURAN PARAFIN DENGAN BAHAN BERBASIS MINYAK - Nanda Jefri AR; Hary Sutjahjono; Dwi Djumharianto (STATOR: Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
World energy demand continue to increase throughout civilization people human. Effort to get alternative energy has long been done to reduce dependency of energy that can not be updated, one of them with solar energy usage as a collector for water heaters. Collector water heater be equipped with the media heat exchanger form Phase Change Material (PCM) to optimize collector performance. There are four ingredients used for PCM is a mixture of paraffin with coconut oil, cooking oli, used coconut oi, and used cooking oil each percentage of the four ingredients with as much paraffin 20% of total volume. Conclusions from this study show that useful energy solar collector be equipped PCM that highest score is solar collector that equipped PCM mix – used coconut oil 20% amount 360,36 watt. With increasing rate of heat transfer on PCM paraffin with a mixture of coconut oil used then temperature change or water also increases so that efficiency sola collector the higher it is. Efficiency solar collektor be equipped PCM the biggest mix is PCM mixed paraffin - used coconout oil 20% amount 62% in the minutes to 360. Keywords : Thermal analysis; Solar collector; An oil-based mixture; PCM